Lead or no lead? Availability, toxicity, sustainability and environmental impact of lead-free perovskite solar cells. Issue 1 (14th December 2020) - Schileo, Giorgio; Grancini, Giulia
Abstract : The presence of lead in perovskite solar cells represents for many a cause of concern. However, alternative elements for lead-free perovskites also present several concerns in terms of toxicity, cost and environmental impact so far neglected. Abstract : Hybrid halide perovskites have taken over the world of new generation photovoltaics (PVs) since their first implementation just a decade ago, thanks to their efficiency comparable to commercial solutions, ease of fabrication, flexibility and versatility. Despite their outstanding performances, the presence of lead represents a severe concern for their future commercialisation, due to its toxicity and associated risks to human health and its environmental impact. Lead-free perovskites offer a potential avenue to circumvent the problem. However, parameters such as material abundance, toxicity and environmental impact of potential lead-substituents are too often neglected. In this review, we put forward a different perspective, focusing on concepts such as cost, availability, sustainability and eco-friendliness required to justify the large-scale use of lead alternatives in the PV industry. Furthermore, comparative case studies with technologies based on lead-containing materials such as lead zirconate titanate, Pb(Zr x Ti1− x )O3, also known as PZT, and CdTe solar panels are provided. Finally, it is argued that the advantages of using lead in photovoltaic panels – when including proper encapsulation and recycling – outweigh the risks associated with its manufacturing.